Evaluasi Kesesuaian Pengelolaan Rekam Medis Dengan Standar Akreditasi Di Rumah Sakit Kabupaten Cirebon - Vadia Nur Afifah Mubaroch; Loura Weryco Latupeirissa; Riantina Luxiarty (MEJORA Medical Journal Awatara, 2024)
Accreditation is recognition given to prayer house because it has made efforts to improve the quality of services on an ongoing basis. The aim of this research is to fid out how appropriate the implementation of medical records in fulfilling accreditation standards at Horpital Cirebon Regency. This type of research uses quantitatve descriptive. The variable in this research is the evaluation of the suitability of medical record administration in meeting accreditation standards at Hospital Cirebon Regency. The object of this research is an evaluation of the suitability of medical record management in fulfilling accreditation standards at Hospital, the subject of this research is medical records management. The data collection technique uses observation with research instrumen namely a checklist sheet. Based on the research results, it is known that from 51 assessment elements that have been studied at Hospital accreditation standards consist of, it was found that standards were not in accordance with hospital accreditation, 3 assessment elements with a percentage of 6%, partially corresponds 7 assessment elements with a percentage of 14%  and 41 assessment elements that were in accordance with hospital accreditation standards with a percentage of 80%. This research can be used as reference material in implementing hospital policies regarding the maintenance of medical records, carrying out regular monitoring regarding the administration of medical records.